2018
DOI: 10.1101/307512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ankyrin-G Regulates Forebrain Connectivity and Network Synchronization via Interaction with GABARAP

Abstract: GABAergic circuits are critical for the synchronization and higher order function of brain networks, and defects in this circuitry are linked to neuropsychiatric diseases, including bipolar disorder, schizophrenia, and autism. Work in cultured neurons has shown that ankyrin-G plays a key role in the regulation of GABAergic synapses on the axon initial segment and somatodendritic domain of pyramidal neurons where it interacts directly with the GABAA receptor associated protein (GABARAP) to stabilize cell surfac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…The Ankyrin-G scaffold is known to be a major organizer of the AIS protein complex. Previous in vivo studies have revealed that giant ankyrin-G functions to stabilize the localization of GABA A R at membrane sectors of both the AIS and the somatodendritic regions of neurons 44,45 . Our demonstration of ankyrin peptides as powerful tools for empirically characterizing GABARAP-GABA A R complex functions implies that further engineering of giant ankyrins or chimeric variants could help to more precisely define the trafficking networks at and beneath the cell membrane micro-domains of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The Ankyrin-G scaffold is known to be a major organizer of the AIS protein complex. Previous in vivo studies have revealed that giant ankyrin-G functions to stabilize the localization of GABA A R at membrane sectors of both the AIS and the somatodendritic regions of neurons 44,45 . Our demonstration of ankyrin peptides as powerful tools for empirically characterizing GABARAP-GABA A R complex functions implies that further engineering of giant ankyrins or chimeric variants could help to more precisely define the trafficking networks at and beneath the cell membrane micro-domains of neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Encoded by the ANK3 gene, Ankyrin-G contains diverse isoforms including small isoforms (100-120 kDa) and large isoforms, in which the larger isoforms (190,270 and 480 kDa) are highly expressed in neurons [281][282][283][284]. Compared with the extensively studied roles of 270 and 480 kDa isoforms in axon initial segment (AIS), nodes of Ranvier (NoR) and inhibitory GABAergic synapses [109,[285][286][287][288][289], the Ankyrin-G 190 kDa isoform (Ankyrin-G-190) was shown to function in regulating the dendritic spine structure and glutamatergic neurotransmission ( [244], Preprint [290]). At synapses, Ankyrin-G-190 forms subsynaptic nanodomains in the spine head surrounding PSDs and within the spine neck to stabilize dendrite and spine architecture both in vitro and in vivo ( [244], Preprint [290]).…”
Section: Ankyrin-gmentioning
confidence: 99%
“…All mice were aged, PND 21-40. C57BL/6J mice were used to develop the assay whereas the knock in Ank3 W1989R model was used as the mouse model of bipolar disorder (Nelson et al, 2018). A subset of the data in this manuscript appeared in Nelson et al 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Oscillations in the gamma band are crucial for proper execution of many cognitive behaviors including attention, memory and sensory processing (György Buzsáki & Wang, 2012; Cardin et al, 2009; Fries, 2009; Siegle et al, 2014; Tallon-Baudry et al, 1998). Abnormalities in gamma oscillations have been observed in a variety of diseases including schizophrenia, bipolar disorder and Alzheimer’s disease (Goutagny et al, 2013; Gruetzner et al, 2013; Klein et al, 2016; Liu et al, 2012; Nelson et al, 2018; Spencer, 2011; Spencer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation